(untitled) - Brown, Lydia (Oxford, 1993)
Aquaculture, the farming of aquatic organisms, either for food or for hobbyists, is a relatively new industry. Man has held fish in ponds and harvested the fruits of the sea for centuries but the knowledge of intensive production methods only developed from the early part of this century.
Keywords: Fishes,Cá; Diseases,Bệnh tật